Influence of CO2 exposure on pH value, electrochemical properties, and the formation of calcium-phosphate on Ti–6Al–4V under adjusted in vitro conditions in DMEM - Virtanen, Sannakaisa; Höhn, Sarah (Applied Surface Science, 2015)
Immersion tests for studying biomaterials surface reactions should be carried out at a pH value of 7.4 and an adjusted blood physiological electrolyte to simulate as far as possible in vivo conditions. The present work deals with surface reactivity of the biocompatible Ti-6Al-4V alloy in <a href="http://www.google.de/url?sa=t&rct=j&q=&esrc=s&source=web&cd=1&ved=0CDAQFjAA&url=http%3A%2F%2Fde.wikipedia.org%2Fwiki%2FDulbecco%25E2%2580%2599s_Modified_Eagle_Medium&ei=69KAU-n7B4SI7Aar54GwAQ&usg=AFQjCNGbok-JZYLdsCKElbJB5kQg5d4w5A&bvm=bv.67720277,d.ZGU">Dulbecco's Modified Eagle Medium (DMEM) and the influence of different immersion conditions on the pH value of solution and thus on the surface charge and calcium-phosphate formation on the oxide covered alloy surface. More specifically, the influence of the temperature (room temperature vs. 37°C) and atmospheric exposure (solution open-to-air vs. solution exposed to 5 % CO2 in air) were investigated. Electrochemical measurements, XPS and ATR-IR studies were carried out for interface characterization. Precipitations of calcium-phosphate (Ca-P) on Ti-6Al-4V in DMEM are formed depending on the atmospheric conditions (presence or absence of CO2). In absence of CO2 strong coverage of the surface by a Ca-P layer takes place; in solution exposed to 5 % CO2, however, only minor amounts of Ca-P are found on the surface. This drastically different behavior can be explained by different surface terminations of OH and TiO2, induced by atmosphere-dependent pH change in solution. In consequence, different surface charges on Ti-6Al-4V can be formed at the interface depending on the type of hydroxides after contact with the electrolyte. Hence, the surface charge influences the interaction with adsorption of charged species and further modifies the oxide properties. The adsorption of the charged cations (Ca2+) and anions (PO43-, HPO42-, H2PO4-) lead to the formation of additional calcium phosphate layers. The pH of the solution is also important. At higher pH the titanium surface is more negatively charged leading to an increased electrostatic interaction with Ca2+ and reduced solubility of the calcium phosphates. Additional experiments indicate that the CO2 content in the atmosphere is significantly more important for the surface reaction than a change in temperature (room temperature vs. 37.5°C).
Keywords: Ti-6Al-4V; pH; CO2; DMEM; calcium-phosphate